Determinants to Stay and Digital Nomad Satisfaction Index in Bali as Digital Nomad Agglomeration Area - Sri Budhi, Made Kembar; Purbadharmaja, Ida Bagus Putu; Yasa, I Nyoman Mahaendra; Suasih, Ni Nyoman Reni (Journal of Posthumanism, 2025)
Digital nomads choose destinations that provide tourism facilities, as well as support for remote workers. Bali, especially Canggu and Ubud, are among the world’s five main destinations for digital nomads. This study aimed to analyse the determinants of the willingness of digital nomads to stay and their satisfaction with staying in Bali. Data collection in this study was carried out using a questionnaire instrument. The analysis was carried out using SEM-PLS regression analysis techniques, composite index analysis to determine the Digital Nomad Satisfaction Index (DNSI) and the Importance-Performance Analysis (IPA). Results analysis of determinants of willingness to stay: It is known that remote working environment, tourism environment, public facilities and services, community attachment, and cost and benefit have a significant positive effect on the willingness of digital nomads in Bali. Digital nomads are generally satisfied living in Bali. Future policies focus on improving performance in terms of visa processing, healthcare services, network expansion opportunities in events, and housing affordability.